Enhanced single-isomer separation and pseudoenantiomer resolution of new primary rim heterobifunctionalized α-cyclodextrin derivatives - Tichá, Iveta; Benkovics, Gábor; Malanga, Milo; Jindřich, Jindřich (Beilstein Journal of Organic Chemistry, 2018)
The synthesis of batch-to-batch reproducible cyclodextrin (CD) derivatives often requires functionalization at specific positions of the CD skeleton. However, the regioselective preparation of this type of CD derivatives remains a challenge in synthetic chemistry. Thus, the present study aimed to prepare all positional regioisomers on the primary rim of homobifunctionalized diazido-α-CDs by selective substitution on the primary rim. Specifically, three positional regioisomers 6A,6B-, 6A,6C-, and 6A,6D-diazido-α-CDs were prepared via different intermediates (using sulfonylation with capping agents, bromination and tosylation). Furthermore, heterobifunctionalized 6A-azido-6X-mesitylenesulfonyl-α-CDs were also synthesized, and all regioisomers were successfully separated by HPLC. Moreover, the heterobifunctionalized α-CD regioisomers were isolated in gram-scale quantities, isomers AB and AC in the form of a pseudoenantiomeric mixture. The pseudoenantiomers AC/CA and AB/BA were resolved on an analytical scale by HPLC–MS at 10 °C. Thus, the presented synthetic and analytical methods for homo- and heterodisubstituted α-CDs are efficient and reproducible for the preparation of various pure regioisomeric CD derivatives. Accordingly, our findings indicate, (i) the versatility of selectively modified azido and mesitylene CD skeletons in preparing new types of α-CD derivatives and (ii) the potential of using resolved α-CD pseudoenantiomers in other research fields such as organocatalysis.
Keywords: diazido-alpha-cyclodextrin; heterobifunctionalized alpha-cyclodextrin; homobifunctionalized alpha-cyclodextrin; regioisomers; regioselectivity